Nominal Wage Contracts, Aggregate and Firm-Specific Uncertainty How High is the Private Gain from Indexation? - Stefan Laséen (Uppsala University, Department of Economics, 2000)
In this paper I investigate to what extent firm-specific uncertainty affects the gain from indexation. Earlier studies have tried to explain wage rigidity by arguing that insiders face little layoff risk due to employment fluctuations caused by aggregate shocks. However, this analysis abstracts from idiosyncratic risk and this seems hard to reconcile with recent microeconomic evidence which shows that firm-specific uncertainty explains a large part of establishments' employment changes. By numerically solving an insider-outsider model I show that the introduction of firm-specific uncertainty increases the gain from indexation considerably (from 0 to 1.5 percent of the wage). It is not evident that the gain from indexation is small enough to support an equilibrium with a constant nominal wage. According to the model, nominal wage contracts should be more prevalent, when layoff is not so costly for the worker, due to high unemployment benefits or short duration of unemployment spells.
Keywords: E24; J41; J63; 330; Indexation; Wage contracts; Insider-outsider models; Lohntheorie; Implizite Kontrakte; Schock; Theorie